High Efficiency Iterative Solver for Modeling Composite Rough Surface Electromagnetic Scattering - Sun, Hua Long; Tong, Chuang Ming; Zou, Gao Xiang (Electromagnetics, 2017)
This article proposes a hybrid iterative solver for modeling composite rough surface electromagnetic scattering. First, a kind of divisional rough surface with the shape of a round water zone embedded in a larger land rough surface is modeled, in which the former is built by Pierson-Moscowitz spectrum; the latter is by Gauss spectrum. Second, aiming at fast computing scattering from this kind of composite rough surface with large scale and fast waving, a hybrid iterative solver is based on forward-backward iterative physical optics with several acceleration strategies, as well as impedance boundary condition. Finally, numerical results show that this hybrid iterative solver can satisfy the requirement for high efficiency, reliable precision in computing scattering from large scale composite rough surface.